2023
DOI: 10.3390/polym15040905
|View full text |Cite
|
Sign up to set email alerts
|

Selective Adsorption of Quercetin by the Sol-Gel Surface Molecularly Imprinted Polymer

Abstract: Quercetin, as one of the most biologically active natural flavonoids, is widely found in various vegetables, fruits and Chinese herbs. In this work, molecularly imprinted polymer (MIP) was synthesized through surface molecular imprinting technology with sol-gel polymerization mechanism on SiO2 at room temperature using quercetin as the template, SiO2 as the supporter, 3-aminopropyltriethoxysilane (APTES) as the functional monomer, and tetraethoxysilane (TEOS) as the cross-linker. The prepared MIP was character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…The regeneration property of MIPs is crucial in practical industrial application. The reusability and the stability of the obtained MIP was determined by measuring the adsorption capacity of the MIP for L-Tyr repeatedly after each adsorption-desorption cycle under the same conditions [38,40]. The adsorption capacity of the MIP, which was reused five times, is shown in Figure 12, which demonstrates that the obtained MIP has excellent stability with a negligible decrease in adsorption capacity.…”
Section: Regeneration Propertymentioning
confidence: 98%
See 1 more Smart Citation
“…The regeneration property of MIPs is crucial in practical industrial application. The reusability and the stability of the obtained MIP was determined by measuring the adsorption capacity of the MIP for L-Tyr repeatedly after each adsorption-desorption cycle under the same conditions [38,40]. The adsorption capacity of the MIP, which was reused five times, is shown in Figure 12, which demonstrates that the obtained MIP has excellent stability with a negligible decrease in adsorption capacity.…”
Section: Regeneration Propertymentioning
confidence: 98%
“…The results indicate that the adsorption of L-Tyr with an MIP is very fast, within 0.5 h, and higher capacity was observed for high initial concentration at adsorption equilibrium. In addition, a longer time was needed to reach adsorption equilibrium for the high concentration, demonstrating that the adsorption process is dependent on concentration [37,38].…”
Section: Adsorption Kineticsmentioning
confidence: 99%
“…It was shown that in the presence of polyethylene glycol (porogen) with an average molecular mass of 10000 Da, the sorption capacity of quercetin by the molecularly-imprinted sample was ~5 µmol/g, the specific surface area was 288.1 m 2 /g, and the imprinting factor was 1.41. It was shown that recovery of quercetin (21-43%) is slightly lower, but the imprinting factor (1.4) is not inferior to that of the similar methods for extracting phenolic compounds [26] and dyes [29] with resorcinol-melamine-formaldehyde and phenol-formaldehyde resins, as well as quercetin with surface-imprinted polymers [30,31]. Modeling of the kinetics and isotherms of quercetin rebinding by the samples, obtained in the presence of polyethylene glycol of different average molecular mass, showed compliance with the pseudo-second-order model and the Freundlich model describing an inhomogeneous surface.…”
Section: Discussionmentioning
confidence: 99%
“…The detection accuracy of the obtained sensor was relatively good, with a recovery rate of 92–117% for practical samples. The sol–gel approach was used for the fabrication of quercetin-based SIPs ( Figure 9 ) [ 101 ], the adsorption could reach equilibrium within 90 min, with a maximum adsorption capacity of 35.7 mg/g. The mechanism for adsorption isotherm and kinetics of SIPs was proved to obey the Freunflich isotherm model and pseudo-second-order kinetics model.…”
Section: Preparation Progress Of Imprinted Polymersmentioning
confidence: 99%